Chromium induced stress conditions in heterotrophic and auxotrophic strains of Euglena gracilis - Rocchetta, Iara (2012)
Oxidative stress parameter and antioxidant defense compound as well as enzyme activity were studied in relation to different Cr(VI) concentrations (0, 10, 20, 40μM) in two strains of Euglena gracilis, one isolated from a polluted river (MAT) and the other acquired from a culture collection (UTEX). Chromium toxicity was measured in the auxotrophic and obligated heterotrophic variants of the two strains. Chromium uptake was higher in auxotrophic cultures, reflected by their higher cell proliferation inhibition and lower IC50 levels compared to heterotrophic ones. In the Cr(VI) treatments a reduction of chlorophyll a and b ratio (Chl a/Chl b) was observed, the ratio of protein to paramylon content was augmented, and total lipid content increased, having the auxotrophic strains the highest values. TBARS content increased significantly only at 40μM Cr(VI) treatment. Unsaturated fatty acids also increased in the Cr(VI) treatments, with the higher storage lipid (saturated acids) content in the heterotrophic cells. The antioxidant response, such as SOD activity and GSH content, increased with chromium concentration, showing the highest GSH values in the heterotrophic cultures and the SOD enzyme participation in chromium toxicity. The MAT strain had higher IC50 values, higher carbohydrate and saturated acid content, and better response of the antioxidant system than the UTEX one. This strain isolated from the polluted place also showed higher GSH content and SOD activity in control cells and in almost all treated cultures. SOD activity reached a 9-fold increase in both MAT strains. These results suggest that tolerance of MAT strain against Cr(VI) stress is not only related to GSH level and/or biosynthesis capacity but is also related to the participation of the SOD antioxidant enzyme.